Asymmetric Catalytic [2, 3] Stevens and Sommelet–Hauser Rearrangements of α‐Diazo Pyrazoleamides with Sulfides. Issue 38 (12th August 2019) - Lin, Xiaobin; Yang, Wei; Yang, Wenkun; Liu, Xiaohua; Feng, Xiaoming
Abstract: Catalytic enantioselective [2, 3] Stevens and Sommelet–Hauser rearrangements of α‐diazo pyrazoleamides with sulfides were achieved by utilizing chiral N, N ′‐dioxide/nickel( II ) complex catalysts. These rearrangements proceeded well under mild reaction conditions, providing rapid and facile access to a series of functionalized 1, 6‐dicarbonyls or sulfane‐substituted phenylacetates with high to excellent enantioselectivities. The catalytic system shows excellent stereocontrol, discriminating between the heterotopic lone pairs of sulfur and controlling both the 1, 3‐proton transfer and the [2, 3]‐σ rearrangement. Abstract : Points of control : Chiral N, N ′‐dioxide/Ni II complexes efficiently catalyze the asymmetric catalytic [2, 3] Stevens and Sommelet–Hauser rearrangements of α‐diazo pyrazoleamides with sulfides. The catalytic system shows excellent stereocontrol, discriminating between the heterotopic lone pairs of sulfur and controlling both the 1, 3‐proton transfer and the [2, 3]‐σ rearrangement.